Efektivitas Media Pop-Up Book Berbasis Bentuk Benda-Benda pada Obyek Wisata Kediri Materi Bangun Ruang Kelas 5 Sekolah Dasar - Sophie Gita Aryani; Wahid Ibnu Zaman; Ika Santia (Mataram University, 2026)
This study aimed to determine the effectiveness of a Pop-Up Book media based on the shapes of objects found at tourist attractions in Kediri in improving the understanding of three-dimensional geometry concepts among fifth-grade elementary school students. The study employed a quantitative approach using the Research and Development (R&D) method with the ADDIE model, focusing on the implementation stage. The research subjects consisted of 26 students who participated in both limited-scale and large-scale trials. Data were collected through pretests and posttests and analyzed using classical learning mastery and N-Gain calculations. The results showed an improvement in learning outcomes, with the average achievement increasing from 66.6% in the pretest (6 students achieving mastery) to 90% in the posttest (20 students achieving mastery), accompanied by an increase in the percentage of learning mastery. The N-Gain scores were categorized as moderate, indicating that the media was sufficiently effective in improving learning outcomes, with N-Gain values of 0.38 in the limited-scale trial and 0.46 in the large-scale trial. The Pop-Up Book media was able to visualize three-dimensional geometry concepts concretely and contextually, making it easier for students to understand the material. In addition, the media enhanced students’ motivation and engagement in the learning process. Therefore, it can be concluded that the Pop-Up Book media based on local tourist attraction contexts is effective for teaching three-dimensional geometry in elementary schools.